Inovasi Aplikasi Pariwisata Cerdas: Penyewaan Layanan Pemandu Wisata di Lembang - Mohamad Dicky Syahputra; Irman Hariman (Universitas Kebangsaan Republik Indonesia, 2023)
This research aims to address the primary challenges in Indonesia's tourism industry, notably the lack of accessibility to accurate information and references. Employing a qualitative approach and Extreme Programming (XP) methodology, the study emphasizes the importance of integrating tour guide services with other tourism services. As a solution, the research proposes the